2020
DOI: 10.1245/s10434-020-08197-z
|View full text |Cite
|
Sign up to set email alerts
|

Pain Control in Breast Surgery: Survey of Current Practice and Recommendations for Optimizing Management—American Society of Breast Surgeons Opioid/Pain Control Workgroup

Abstract: is a part time employee for Avelas Biosciences-a company that develops imaging techniques to be used to identify margins during breast surgery. Dr. Lee Wilke is founder and minority stock owner for Elucent Medical-a tumor localization device company.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The current study adds to our understanding of pain management requirements in this population. There is substantial variation in opioid usage, particularly in breast surgery, 18 where recent work illustrates that opioid prescribing continues to outpace consumption 19 , and guidelines aimed at optimizing multimodal pain regimens are very much needed 20 . Furthermore, our consumption data suggest that prescription sizes may be further reduced without compromising patient satisfaction.…”
Section: Discussionmentioning
confidence: 94%
“…The current study adds to our understanding of pain management requirements in this population. There is substantial variation in opioid usage, particularly in breast surgery, 18 where recent work illustrates that opioid prescribing continues to outpace consumption 19 , and guidelines aimed at optimizing multimodal pain regimens are very much needed 20 . Furthermore, our consumption data suggest that prescription sizes may be further reduced without compromising patient satisfaction.…”
Section: Discussionmentioning
confidence: 94%
“…A recent survey of 609 members of the American Society of Breast Surgeons found that approximately 80% of surgeons prescribed opioids after lumpectomy, with most prescribing a range of 1-10 tablets, and a minority prescribing > 31 tablets. 1 Despite this practice, there is no clear evidence that opioids are necessary for adequate pain control after lumpectomy/SLNB. An increasing number of studies suggest that non-opioid medications such as non-steroidal antiinflammatory drugs (NSAIDs) and/or acetaminophen can provide effective pain control after many commonly performed ambulatory procedures.…”
mentioning
confidence: 99%
“…Surgeons who avoid NSAIDs likely worry about hematoma formation, although the literature does not support this concern. [5][6][7] There was significant variability in the use of regional anesthesia for mastectomies with and without reconstruction despite its documented efficacy. [8][9][10][11][12][13] Thirty-three percent of surgeons reported never using nerve blocks for patients undergoing mastectomies with reconstruction, and 43% of surgeons did not use this analgesic strategy at all for patients undergoing mastectomies without reconstruction.…”
mentioning
confidence: 99%
“…The only procedures for which the workgroup recommends prescribing more than 10 tablets are ALND (20 or fewer tablets), mastectomy with or without axillary surgery (20 or fewer), and mastectomy with reconstruction (30 or fewer). 5 In addition to making these prescribing recommendations, the ASBrS workgroup encourages the use of regional anesthesia and strongly recommends the use of Enhanced Recovery After Surgery (ERAS) programs. Only a minority (14%) of respondents in this study reported using ERAS protocols.…”
mentioning
confidence: 99%
See 1 more Smart Citation